Pengembangan Sumber Daya Manusia yang Unggul Berbasis Pumping-HR Model - Ramly, Amir Tengku (Jurnal Manajemen, 2016)
This study is an evaluative framework of Stufflebeam CIPP evaluation model, with evaluation components: context, input, process and product, which involve trainees in IPB human resource development program for 3 years running.Human resource development training program based on the model of IPB pumping is a useful program for employment and self, which have an impact on performance. In the context of this program supports the goals of human resource development IPB. In this program input is designed according to the needs of HR IPB to (1) the strengthening of values and beliefs, (2) the strengthening of competence, and (3) encourage the successful behavior in terms of responsibility, professionalism and friendliness of the work. In the preferred process of this program and fun for participants and products (output and outcome) can benefit from this program and give a clear impact to the performance of the employee